Expressões Idiomáticas bilíngues relativas ao campo lexical do vestuário: uma reflexão sobre suas metáforas e metonímias - Lodi, Ariane [UNESP] (2014)
This research focuses on Idioms related to the clothing lexical field, with a multidisciplinary feature, which interrelate Lexicology/Lexicography, Phraseology and Cognitive Semantics, the latter especially when it is related to conceptual metaphors and metonymies. From a cognitivist view, based on the evidence that most of our experience and perception is shared by all human beings, it is believed that different languages and cultures may share same or similar metaphors and metonymies. Therefore, the aim of this thesis is to conduct a contrastive analysis between metaphors and metonymies that underlie Italian Idioms and their translational correspondents in Portuguese, to investigate to what extent this premise may be confirmed. This inquiry is primarily based on Zuluaga (1980), Lakoff and Johnson (1980, 2002), Gibbs (1994), Tonfoni and Turbinati (1995), Corpas Pastor (1996), George (1997, 2001), Xatara (1998), Kövecses (2005, 2010) and Malho (2010). Approximately 160 Italian idioms derived from 49 lexical items related to clothing. They were selected from Italian monolingual dictionaries, furthermore their definitions were provided and usage examples were collected from web. After that, an analysis of types of equivalence as well as an investigation of possible motivations that gave rise to them were performed. As a final product of our study, an inventory of clothing-related idioms was produced which intends to fill some gaps in Italian and Portuguese languages in regard to bilingual material on idioms. On this basis, initial theoretical hypothesis was confirmed